2008
DOI: 10.1002/hyp.7089
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of nutrient management and decrease in paddy field area on groundwater nitrate concentration: a case study at the Nasunogahara alluvial fan, Tochigi Prefecture, Japan

Abstract: Abstract:In order to help evaluate the trends in the NO 3 -N concentration in groundwater with a view to preventing further degradation in water quality in the future, a distributed groundwater quality model was constructed for the Nasunogahara basin. The best fit for the groundwater table elevations by the flow component of the model was achieved with average mean absolute errors (MAEs) of 0Ð92 m for the calibration period and 0Ð83 m for the validation period. Moreover, the best fit for the NO 3 -N concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Hence, the distribution and transport of nitrate nitrogen based on agricultural irrigation has been studied in South China [23] and North China [24]. Various methods have been presented for determining and monitoring nitrate nitrogen concentrations in groundwater to provide guidance for the development of water quality management strategies [25], identify trends in groundwater nitrate concentrations and prevent further groundwater quality deterioration [26]. Researchers have suggested that both shallow and deep groundwater chemistry should be monitored and that the recharge areas associated with regional flow systems are extremely vulnerable to nitrate pollution [27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the distribution and transport of nitrate nitrogen based on agricultural irrigation has been studied in South China [23] and North China [24]. Various methods have been presented for determining and monitoring nitrate nitrogen concentrations in groundwater to provide guidance for the development of water quality management strategies [25], identify trends in groundwater nitrate concentrations and prevent further groundwater quality deterioration [26]. Researchers have suggested that both shallow and deep groundwater chemistry should be monitored and that the recharge areas associated with regional flow systems are extremely vulnerable to nitrate pollution [27].…”
Section: Introductionmentioning
confidence: 99%
“…6 and 7), the simulated values trended higher than the literature observations. These high leaching rates from the simulation could be attributed to the existence of groundwater at a depth of 1 m in the study region (Somura et al, 2008;Yamanaka et al, 2003), the relatively high porosity of Andosols, and the high N input with the limited crop N uptake. In the case of N 2 O emission, observations in uplands were in the range of 0.07-23.3 kg N 2 O-N ha −1 yr −1 for Japan (Akiyama et al, 2006) and those of paddy fields were 0.1-17.9 kg N 2 O-N ha −1 yr −1 from 43 field observations under 90-600 kg N ha −1 yr −1 fertilization.…”
Section: Long-term Impacts Of Intensive Manure Applicationmentioning
confidence: 93%
“…Highly intensive livestock system was generally contributed to the signification of environmental degradation (Peyraud et al, 2014). High nitrate concentration in ground water has been reported in livestock regions (Somura et al, 2008). Vergé et al (2007) reported that intensive livestock has increased greenhouse gas emission at twice the rate of traditional farming systems, and at more than six times the rate of production based on grazing.…”
Section: Introductionmentioning
confidence: 98%
“…Reflecting this difference in land use, NO 3 -N concentrations in group 4 groundwaters were higher than those in the other groups (Table 1). We inferred that these higher concentrations reflected the high nitrogen load associated with livestock farming (e.g., [27]). It can be readily seen that the contribution of infiltration from paddy rice field to groundwater recharge was smaller for group 4 than for group 2 groundwaters.…”
Section: Characterization Of Groundwater Using Sommentioning
confidence: 99%
“…Previous studies of groundwater in this area have focused on spatio-temporal variations in the groundwater quality [25,26], groundwater nitrate dynamics [27], and the groundwater budget, as simulated by a 2D horizontal model [28]. Stable isotope ratios of water have been effectively used to identify recharge sources of the groundwater in the central part of the fan [24], but the applicability of the method to the whole fan remains to be demonstrated, and how different recharge sources influence the flow of groundwater in the aquifer is still unclear.…”
Section: Introductionmentioning
confidence: 99%